Polymerization shrinkage, modulus, and shrinkage stress related to tooth-restoration interfacial debonding in bulk-fill composites. Issue 4 (April 2015) - Kim, Ryan Jin-Young; Kim, Yu-Jin; Choi, Nak-Sam; Lee, In-Bog
Abstract Objectives The aim of the present study was to measure the polymerization shrinkage, modulus, and shrinkage stress of bulk-fill and conventional composites during polymerization and to investigate the relationship between tooth-composite interfacial debonding and shrinkage stress of the composites. Methods Polymerization shrinkage, dynamic modulus, and shrinkage stress of two high-viscosity bulk-fill (SonicFill (SF)/Tetric N-Ceram Bulk-Fill (TNB)) and two low-viscosity bulk-fill composites (Filtek Bulk-Fill (FB)/SureFil SDR Flow (SDR)) as well as one high-viscosity conventional (Filtek Z250 (Z250)) and one low-viscosity conventional composite (Filtek Z350 XT Flowable (Z350F)) were measured using custom-made instruments. Acoustic emission (AE) analysis was performed to evaluate the tooth-composite interfacial debonding during polymerization of the composites in Class 1 cavities on extracted third molars. Results The low-viscosity composites exhibited higher shrinkage and lower modulus than the high-viscosity composites. Polymerization shrinkage at 10 min ranged between 2.05% (SF) and 3.53% (Z350F). Polymerization shrinkage stress values at 10 min ranged between 1.68 MPa (SDR) and 3.51 MPa (Z350F). The number of AE events was highest in Z350F and lowest in SDR. Conclusions Composites that exhibited greater polymerization shrinkage stress generated more tooth-composite interfacial debonding. In contrast to similar outcomes among the high-viscosity composites (conventional: Z250, bulk-fill: TNB and SF), the low-viscosity bulk-fill composites (FB and SDR) demonstrated better results in terms of polymerization shrinkage stress and tooth-composite interfacial debonding than did the low-viscosity conventional composite (Z350F). Clinical significance Despite the better performance by some of the bulk-fill composites, clinicians should be aware that the bulk-fill composites are not perfect substitutes for conventional composites.